The Open Mind: George Soros: A Capitalist on 'The Capitalist Threat'
In the first interview with Richard Heffner on “Open Mind” George Soros talks about his cover story for The Atlantic Monthly titled “The Capitalist Threat” and the philosophical and economical ideas behind the article.